PENGARUH PERPUTARAN KAS TERHADAP LIKUIDITAS SEKTOR KEUANGAN PADA PT BANK CENTRAL ASIA, Tbk. - Iis Dewi Herawati; Herlina (Lembaga Pengembangan Kinerja Dosen, 2022)
This scientific research is intended to analyze and determine the effect of cash flow turnover on liquidity in a company engaged in banking, in this case at Bank Central Asia, Tbk. As is known, that positive cash flow can affect the level of company liquidity. On this matter, a research was conducted that aims to analyze the significance of the effect of cash turnover on the company's liquidity with various methods. The methods include X-Y Correlation Test and Regression Parameter Test. In the X-Y Correlation Test, the R number of 0.639 explains the strong relationship between Cash Turnover (X) and Liquidity (Y) (above 0.05). The number of R square / determinant coefficient is 0.408. This means that 40.83% of the variation of Liquidity (Y) can be explained by variations of Cash Turnover (X) while the rest (100% - 40.83% = 59.17%).